Passive earth pressure determination : application of the corresponding state theorem for calculating upper-bound values - Macuh, Borut (Acta geotechnica Slovenica, 2010)
The validity of some limit state solutions, when strictly applied to the basic corresponding state theorem (Caquot, 1934), is limited and valid only for simpler limit states, where stress vectors are either perpendicular to the boundary surfaces or when the direction of stress eigenvalue trajectories in transformation are preserved (Michalowski, 2001). The theorem of corresponding states allows us, in some cases, to attain solutions belonging to the limit states for cohesive-friction materials with the transformation of the known boundary of elasto-plastic solutions of limit states for pure friction materials. We demonstrated that for the selected kinematically admissible model, in general cases of boundary stresses, the indirect application of the corresponding states theorem in modified form is permitted.To determine this, we applied the kinematic approach of limit state analysis and used the upper-bound theorem for determining passive earth pressures. The results of our analyses show that incautious application of the corresponding state theorem in its basic form and for general cases is in admissible because the results obtained can be correct only coincidentally, depending on the boundary conditions
Keywords: geotehnika; korespondenčno stanje; mehanika tal; mejna analiza; pasivni tlak; zemeljski tlak; zgornja vrednost